2020
DOI: 10.31491/csrc.2020.12.064
|View full text |Cite
|
Sign up to set email alerts
|

Gastrointestinal perforation in COVID-19 patients – case series and review of the literature

Abstract: Severe acute respiratory syndrome coronavirus-2 (SARS-CoV 2) involving the respiratory tract started in 2019 in Wuhan, China but spread to almost all parts of the world to the extent that it was declared a pandemic by WHO. As more and more cases are detected, the involvement of systems other than respiratory was observed and nearly 5 to 50 % of patients have abdominal symptoms like pain and diarrhea. During the course of treatment, few patients developed a rare complication of gastrointestinal perforation. Thr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 15 publications
(18 reference statements)
3
3
0
Order By: Relevance
“…Increased CRP is also reported in the previous studies ( 5 , 11 , 26 ) and is known as a marker of poor prognosis among COVID-19 patients ( 27 , 28 ). Similar to the previous studies ( 7 , 8 ), D-dimer was also significantly increased among our patients, surpassing 5,000 ng/mL in some patients. D-dimer is a predictive factor of disease severity and mortality among COVID-19 patients ( 8 , 13 , 27 , 28 ) and is also suggestive of thrombotic microangiopathy ( 13 , 14 ).…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Increased CRP is also reported in the previous studies ( 5 , 11 , 26 ) and is known as a marker of poor prognosis among COVID-19 patients ( 27 , 28 ). Similar to the previous studies ( 7 , 8 ), D-dimer was also significantly increased among our patients, surpassing 5,000 ng/mL in some patients. D-dimer is a predictive factor of disease severity and mortality among COVID-19 patients ( 8 , 13 , 27 , 28 ) and is also suggestive of thrombotic microangiopathy ( 13 , 14 ).…”
Section: Discussionsupporting
confidence: 92%
“…The symptoms and signs of intestinal ischemia were initiated 7 days following the respiratory manifestations of COVID-19. The precedence of respiratory manifestations has also been mentioned in the previous studies ( 6 , 7 , 10 , 11 , 26 ). However, some studies report the concomitant PCR confirmation of COVID-19 and intestinal ischemia ( 7 , 8 , 12 ).…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…We found 18 perforations in patients not treated with IL-6 inhibitors. Of these 18 cases, 12 were lower GI perforations ( [1] , [2] , [3] , [4] , [5] , [6] , [7] , [8] , [9] , [10] ), 6 were perforated gastroduodenal ulcers ( 8 , [11] , [12] , [13] , [14] ). One of these after embolization of a bleeding ulcer ( 15 ).…”
Section: Discussionmentioning
confidence: 99%
“…Fortunately, recent studies [14] have found that in some stable patients with a confined and limited perforation, nonoperative therapy may be utilized successfully. Nonoperative approaches can be considered if GI perforation is confined and possibly treated successfully by combination of antibiotics intervention, and if surgical intervention is required, the appropriate method can be chosen on an individual basis.…”
Section: A 3bmentioning
confidence: 99%